Looking at others in national policy-making: the construction of reference groups in Portugal and Spain from 2008 to 2013. Issue 3 (27th May 2019) - Pi Ferrer, Laia; Alasuutari, Pertti; Tervonen-Gonçalves, Leena
ABSTRACT: Why is it that when debating the economic crisis, actors in the Portuguese parliament invoke more frequently countries affected by the crisis, whereas actors in the Spanish parliament invoke economically well-off countries more often? This article explores this mystery by studying how and why certain countries are evoked in the decision-making process. The analysis reveals that the actors mention different countries to contextualize the nation. We argue the actors in these two countries resort to different reference groups to identify or distance the nation in this concrete period even if they present similar challenges.